(untitled) (Research, Society and Development, 2021)
The h-index was presented by the scientific community to measure researchers’ contribution quantitatively. Given its wide existence, the objective of this article is to analyze the panorama of the most influential works that use the h-index in its approach, published throughout the decade from 2011 to 2020. The proposed methodology consisted of a selection, in Scopus, highlighting the author with the highest h-index and then selecting the most cited article in the database annually. As a result, it was possible to observe some patterns in the authors’ publications that remained relevant, as well as the nature of journals in the health area. As conclusions, it is noteworthy that the authors that stand out over the years do not work with the h-index, and thus, the themes of the highlighted works also do not prioritize the index, they only use it for application in your area of research.